Influence of environmental and anthropogenic parameters on thallium oxidation state in natural waters. (April 2018) - Campanella, Beatrice; D'Ulivo, Alessandro; Ghezzi, Lisa; Onor, Massimo; Petrini, Riccardo; Bramanti, Emilia
Abstract: The abandoned mining area of Valdicastello Carducci (Tuscany, Italy) is characterized by the massive presence of thallium in the acid mine drainages and in the valley stream crossing the region. We previously found that Tl(III), generally considered the less stable oxidation state of thallium, is present both in the stream and in tap water distributed in the area, whereas acid mine drainages only contain Tl(I). These findings posed some concern related to the reactivity and dispersion of this toxic element in the environment. Since the valence state of thallium determines its toxicity, distribution and mobility, the study of thallium redox speciation appears crucial to understand its environmental behaviour. In this work, water samples collected from the mine drainages and the contaminated stream were adopted as model to study the distribution of aqueous Tl(I)/Tl(III) as a function of light exposure and solution properties and composition. The influence of three light sources and organic acids was evaluated. Thallium speciation was also assessed in tap water after treatment with common oxidizing agents, and in the rust crust collected from the public waterworks. Graphical abstract: Image Highlights: Thallium (III) has been found in considerable amounts in tap and surface water. UV promotes oxidation of Tl(I) to Tl(III) in standard solutions and real samples. LED at 379 nm oxidised efficiently Tl(I) only in AMD and surface water. Chlorine-based oxidants promote the quantitative conversion of Tl(I) to Tl(III). The results can be helpful to better understand Tl mobility and behaviour.